Laser focus depth adaptation for decapsulation of copper wirebonded devices - Kor, Katherine Hwee Boon (2015)
Although pre-laser decapsulation reduces the time to acid exposure for subsequent chemical decapsulation of copper wirebonded devices, it can result in severely damaged or broken copper wirebonds if carried out at a focused depth followed by chemical decapsulation. Thin quad flat packages (TQFPs) of dimensions 22 mm × 22 mm, with copper wirebonds were pre-laser decapped (Nd:YAG laser, 1064 nm) at three depths of focus, at focus, (z-0.5) mm and (z-1) mm. Reducing the laser focus depth by 1 mm, followed by subsequent chemical decapsulation, resulted in the least damage to copper wirebonds. Average percentage reduction in copper wirebond diameter after complete (laser and chemical) decapsulation is about 2.30%.